A liquid chromatography–mass spectrometric method for the quantification of azithromycin in human plasma. (15th March 2013) - Ben‐Eltriki, Mohamed; Somayaji, Vishwa; Padwal, Raj S.; Brocks, Dion R.
ABSTRACT: A liquid chromatographic mass spectrometric assay for the quantification of azithromycin in human plasma was developed. Azithromycin and imipramine (as internal standard, IS) were extracted from 0.5 mL human plasma using extraction with diethyl ether under alkaline conditions. Chromatographic separation of drug and IS was performed using a C18 column at room temperature. A mobile phase consisting of methanol, water, ammonium hydroxide and ammonium acetate was pumped at 0.2 mL/min. The mass spectrometer was operated in positive ion mode and selected ion recording acquisition mode. The ions utilized for quantification of azithromycin and IS were m / z 749.6 (M + H) + and m / z 591.4 (fragment) for azithromycin, and 281.1 m / z for internal standard; retention times were 6.9 and 3.4 min, respectively. The calibration curves were linear ( r 2 > 0.999) in the concentration ranges of 10–1000 ng/mL. The mean absolute recoveries for 50 and 500 ng/mL azithromycin and 1 µg/ mL IS were >75%. The percentage coefficient of variation and mean error were <11%. Based on validation data, the lower limit of quantification was 10 ng/mL. The present method was successfully applied to determine azithromycin pharmacokinetic parameters in two obese volunteers. The assay had applicability for use in pharmacokinetic studies. Copyright © 2013 John Wiley & Sons, Ltd.